Institutions, imagination and reality in the XXI century - Moneta, Carlos (2000)
Opines that regional institutions such as SELA have the fundamental task to contribute to solving, in the best possible way, the situations that arise from the current international scenario, without, however, becoming entrapped by them. Warns that the analysis of developments as well as the preparation of proposals must take into account the cultural factor, since 'the values and behavioural modalities of each social group make up the universe in which economic reasoning can be interpreted'.